A hierarchical porous Janus structure carbon-graphene aerogel and preparation method thereof

By adopting layered porous Janus structure carbon-graphene aerogel, the problem that existing carbon-based interface evaporation materials are difficult to prevent the generation of salt scale during efficient evaporation is solved, and efficient and salt-resistant water evaporation performance is achieved.

CN118771363BActive Publication Date: 2025-04-11NAVAL UNIV OF ENG PLA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410770982.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2025-04-11
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

The existing carbon-based interface evaporation materials are difficult to prevent the generation of salt scale while maintaining high efficiency, affecting the evaporation rate and efficiency.

Method used

A layered porous Janus structure carbon-graphene aerogel is used, which uses the ice crystal template method to prepare aerogel with hydrophobic and hydrophilic bilayer structures through the combination of chitosan, furfural and graphene oxide, thereby avoiding the complexity of multi-step preparation.

Benefits of technology

It achieves efficient water evaporation, with an evaporation rate of 3.66kg·m-2·h-1, and maintains efficient evaporation performance in seawater and high brine without salt scale generation, and has good salt resistance and self-cleaning and dissolved salt properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771363B_ABST
    Figure CN118771363B_ABST
Patent Text Reader

Abstract

The present invention relates to a layered porous Janus structure carbon-graphene aerogel and a preparation method thereof, comprising the following steps: chitosan is dispersed in an acid solution to form a sol; a graphene oxide dispersion is added to the sol, stirred to form a suspension having reduced graphene oxide sheets, furfural is added, and a viscous sol liquid is obtained and then molded; after the mold is inverted, the reduced graphene oxide sheets are deposited on the bottom of the mold to form a layer, and the sample in the mold forms a double-layer structure; the mold is placed on a pre-frozen copper block, and gradient freeze drying is performed after the sample is frozen to form a gel to obtain a chitosan-furfural-graphene hybrid organic aerogel; the organic aerogel is placed in a high-temperature cracking furnace, heated and carbonized, annealed, and cooled to obtain the aerogel. The present invention adopts a one-pot method, which effectively avoids the complexity of preparing the Janus structure by a multi-step method, and the prepared aerogel has the excellent salt resistance and interface evaporation performance of the Janus structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a hierarchical porous Janus structure carbon-graphene aerogel and a preparation method thereof. Background Art

[0002] To date, there are still many areas and islands around the world that are severely short of fresh water resources. Using abundant seawater or brackish groundwater for desalination and purification to produce clean fresh water is considered to be one of the most effective ways to solve the water shortage crisis. In recent years, solar-driven interfacial evaporation technology (SIE), which uses floating structures to locally confine heat to the interface, has developed rapidly. It is a sustainable and pollution-free way to desalinate seawater and is considered to be an efficient way to desalinate seawater and produce fresh water in the future. However, the inevitable pollution and salt accumulation in the marine environment will seriously affect the evaporation rate and efficiency of the evaporation material. Although many scholars have previously developed interfacial evaporation materials with various structures, there are still key challenges in preventing the formation of salt scale while maintaining efficient evaporation.

[0003] Among many types of materials, carbon-based materials are popular in the field of SIE due to their wide-band light absorption ability, high stability and low cost. In the past few years, many scholars have greatly improved the evaporation rate of carbon-based SIE materials through strategies such as composite material design, reducing evaporation enthalpy, and constructing special-shaped structures. However, the water evaporation rate of most reported carbon-based SIE materials is still between 1.47 and 3 kg m -2 h -1 (1kW·m -2 ) range. In order to improve the evaporation rate, the natural structural advantage has led to the emergence of a series of biomass structured carbon-based SIE materials. In the prior art, Yue Bian et al. simply carbonized biological bamboo to obtain a three-dimensional structured carbon material with a 1-sun light (1kW·m -2 ) The water evaporation rate reaches 3.13 kg m -2 h -1 . After carbonization, bamboo maintains a unique natural layered cell structure, which effectively reduces the evaporation enthalpy and thermal radiation loss during evaporation. However, although this type of biomass carbon material can provide a good internal structure, it often depends on the original structure of the organism, so the structure cannot be artificially designed and regulated. In addition, the continuous evaporation of seawater will inevitably lead to an increase in the salt concentration on the surface area of ​​the evaporation material. Long-term salt accumulation will block the pores of the material and hinder the transport of water and the escape of evaporated steam. The high reflectivity of salt scale will also significantly affect light absorption and reduce the evaporation performance of the material. Therefore, the salt-resistant structure design of carbon-based SIE materials is particularly important.

[0004] In recent years, great progress has been made in salt-tolerant SIE materials inspired by biological structures. Inspired by the Janus structure of the lotus-like organism, a hydrophobic surface with natural non-wetting properties is an effective way to prevent salt water penetration. The innovative strategy of the hydrophobic interface effectively prevents the accumulation of salt. In the prior art, Ning Xu et al. selected a micron-pore copper foam as a substrate and coated Al2O3 and carbon nanoparticles on the surface to assemble a hierarchical carbon-based SIE material (WHS) inspired by water lilies; WHS achieved 1.28 kg m in 10 wt% brine. -2 h -1 (1kW·m -2 ) evaporation rate; Zhipeng Jin et al. used 3D printing technology to prepare a three-dimensional chiral twisted carbon nanotube CNTs aerogel matrix, and then sprayed superhydrophobic SiO2 on its surface to prepare a Janus structure evaporation material, which achieved 1.422 kg m in 20 wt% brine. -2 h -1 (1kW·m -2 ) evaporation rate. Although the above examples well demonstrate the high evaporation performance of the bionic Janus structure in high-concentration brine. However, most of these types of Janus structure materials often require two or more steps to prepare hydrophilic materials and hydrophobic materials separately, and finally combine the two materials to form a Janus structure, and the preparation process is relatively complicated.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a hierarchical porous Janus structure carbon-graphene aerogel and a preparation method thereof, which effectively avoids the complexity of preparing the Janus structure by a multi-step method, while also having the excellent salt resistance and interface evaporation performance of the Janus structure.

[0007] A first aspect of the present invention provides a method for preparing a hierarchical porous Janus structure carbon-graphene aerogel, comprising the following steps:

[0008] S1. Dispersing chitosan in an acid solution and stirring until it is completely dissolved to form a sol;

[0009] S2, adding the graphene oxide dispersion to the sol, stirring to form a suspension having reduced graphene oxide sheets, then adding furfural, stirring until completely mixed, and then casting a viscous sol solution;

[0010] S3, after the mold is poured, it is allowed to stand until the reduced graphene oxide sheets are deposited on the bottom of the mold to form a layer, and the sample in the mold forms a double-layer structure;

[0011] S4, placing the mold on a pre-frozen copper block, and performing gradient freeze drying after the sample is frozen to form a gel, to obtain a chitosan-furfural-graphene hybrid organic aerogel;

[0012] S5. Placing the organic aerogel in a high-temperature pyrolysis furnace, filling it with inert protective gas, heating it for carbonization, annealing it after carbonization, and then naturally cooling it to room temperature to obtain a hierarchical porous Janus structure carbon-graphene aerogel.

[0013] Preferably, in step S1, the acid solution is an aqueous solution of glacial acetic acid, more preferably an aqueous solution of 2 wt % glacial acetic acid.

[0014] Preferably, the mass ratio of the chitosan to the aqueous solution of glacial acetic acid is 1:(40-60), more preferably 1:(45-55).

[0015] Preferably, in step S2, the concentration of the graphene oxide dispersion is 1-5 mg / ml, for example: 1 mg / ml, 2 mg / ml, 2.5 mg / ml, 3.3 mg / ml, 5 mg / ml.

[0016] Preferably, step S2 comprises:

[0017] S21, adding the graphene oxide dispersion liquid dropwise to the sol while stirring, and stirring until a suspension having reduced graphene oxide sheets is formed;

[0018] S22, adding furfural dropwise to the suspension, stirring until completely mixed, and then casting into a mold after obtaining a viscous sol liquid.

[0019] Preferably, in step S2, the mass ratio of furfural to chitosan is 1:(3-6), more preferably 1:4.

[0020] Preferably, step S3 comprises: after the mold is poured, the mold is left to stand in an open state, and the reduced graphene oxide sheets are deposited to the bottom of the mold to form a layer, and the sample in the mold forms a double-layer structure; wherein the upper layer is the chitosan-furfural sol, and the lower layer is the reduced graphene oxide sheets.

[0021] Preferably, step S4 comprises:

[0022] S41, pre-freezing and cooling the copper block, placing a mold on the copper block, and directional freeze-casting a directional hole structure through an ice crystal template;

[0023] S42. After freezing to form a gel, the sample is placed in a freeze dryer and freeze-dried from -45°C to 30°C with a gradient of 5°C to obtain chitosan-furfural-graphene hybrid organic aerogel.

[0024] Preferably, step S5 comprises:

[0025] S51, placing the organic aerogel in a high-temperature pyrolysis furnace, filling it with inert protective gas, raising the temperature from room temperature to 300°C at a rate of 2-4°C / min, and then raising the temperature to 800-1200°C at a rate of 4-6°C / min for carbonization;

[0026] S52. After the carbonization is completed, annealing is performed to 500°C at a rate of 2°C / min and naturally cooled to room temperature to obtain a hierarchical porous Janus structure carbon-graphene aerogel.

[0027] The second aspect of the present invention provides a hierarchical porous Janus structure carbon-graphene aerogel, which is prepared by the above-mentioned preparation method.

[0028] The third aspect of the present invention provides the application of the above-mentioned hierarchical porous Janus structure carbon-graphene aerogel in the field of seawater desalination.

[0029] Beneficial effects:

[0030] (1) The present invention utilizes the dual chemical reaction principle of the free amino groups of chitosan to prepare a unique biomimetic Janus hierarchical porous chitosan (chitosan)-furfural (furfural)-graphene (GO) hybrid aerogel-derived carbon-graphene composite aerogel (CFrGO) by a precipitation process and a freeze-casting method. The one-pot method for preparing the Janus structure effectively avoids the complexity of the multi-step preparation method, while also having the excellent salt resistance and interface evaporation performance of the Janus structure.

[0031] (2) The photothermal conversion layer composed of reduced graphene oxide (rGO) in the CFrGO aerogel structure prepared by the present invention can achieve efficient photothermal conversion, and the hydrophobic interface effectively prevents seawater from entering to achieve a good anti-salt clogging effect, and the hydrophilic layer achieves a good continuous water supply. This special hierarchical porous structure in the CFrGO aerogel changes the evaporation form of water molecules and significantly reduces the evaporation enthalpy; CFrGO aerogel achieves 3.66 kg·m -2 ·h -1 The evaporation rate and steam generation efficiency of 97% of CFrGO aerogel in Bohai Sea water and 10% simulated salt water reached 3.01 kg·m -2 ·h -1 and 3.16 kg·m -2 ·h -1 High evaporation rate without any salt scaling.

[0032] (3) The CFrGO aerogel prepared by the present invention also has fast photothermal response performance under dark light and self-cleaning salt-dissolving performance.

[0033] (4) The CFrGO aerogel prepared by the present invention has the stability, reusability and photothermal conversion performance of carbon materials, and also has the excellent thermal insulation performance of the aerogel structure, providing a new option for the development of efficient, stable and salt-resistant SIE seawater desalination technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 A flow chart for preparing the hierarchical porous Janus structure carbon-graphene aerogel provided by the present invention.

[0036] Figure 2 Schematic diagram of the bionic-inspired CFrGO aerogel provided by the present invention; wherein, (a) is a simulated structure diagram of the CFrGO aerogel; (b) is an optical picture of the surface and bottom layer of Victoria amazonica; (c) is a top-down SEM picture of the rGO layer of the CFrGO aerogel; (d) is a top-down SEM picture of the cross-section of the directional pore layer of the CFrGO aerogel; (e) is a side-view cross-sectional SEM picture of the directional pore layer of the CFrGO aerogel; (f) is a high-magnification SEM picture of the sidewalls of the directional pores of the CFrGO aerogel; and (g) is a light absorption rate curve of the rGO photothermal conversion layer of the CFrGO aerogel in the wavelength range of 200-2500nm.

[0037] Figure 3 The structural characterization result diagram of the CFrGO aerogel provided by the present invention; wherein, (a) is the drying shrinkage, carbonization shrinkage curve and carbonization mass reduction rate curve of the CFrGO sample; (b) is the statistical data of the density of the CFrGO sample; (c) is an optical photograph of a CFrGO / 2.5 sample placed on a leaf; (d) to (m) are microstructural SEM images of the side walls of the rGO layer and the directional pore layer of samples with different GO contents, wherein, (d) and (i) represent CFrGO / 1, (e) and (j) represent CFrGO / 2, (f) and (k) represent CFrGO / 2.5, (g) and (l) represent CFrGO / 3.3, and (h) and (m) represent CFrGO / 5.

[0038] Figure 4The composition and physical property characterization results of the CFrGO aerogel provided by the present invention are shown in the figure; wherein, (a) is the Raman spectrum of the CFrGO sample (CFrGO / 2.5 aerogel); (b) is the XRD spectrum of the hydrophilic layer and the hydrophobic layer; (c) is the energy dispersion spectrum (EDS) curve (the inset is the SEM image and the EDX elemental mapping results of the C, O elements); (d) is the FTIR spectrum of the sample; (e) is the nitrogen adsorption / desorption isotherm of CFrGO / 2.5; (f) is the pore size distribution curve; (g) is the thermal conductivity; (h) and (i) are contact angle tests; (j), (k) and (l) are the thermogravimetric TG and DTG curves of CFrGO / 2.5, wet CFrGO / 2.5 and pure water, respectively.

[0039] Figure 5 The evaporation performance test and characterization result diagram of the sample provided by the present invention; wherein, (a) is the dark evaporation rate and equivalent evaporation enthalpy of the sample; (b) and (c) are the OH bond vibration peaks of the Raman spectra of pure water (the inset is a schematic diagram of the structure of water) and CFrGO / 2.5, respectively; (d) is the evaporation mass of the sample under 1 sun; (e) is the evaporation rate and efficiency of the sample under 1 sun.

[0040] Figure 6 The temperature field distribution diagram of the sample evaporation experiment under 1 sun provided by the present invention; wherein, (a) represents CFrGO / 1, (b) represents CFrGO / 2, (c) represents CFrGO / 2.5, (d) represents CFrGO / 3.3, (e) represents CFrGO / 5, and (f) represents CFrGO / 2.5R.

[0041] Figure 7 The evaporation performance test and temperature response curve diagram of the sample provided by the present invention under low light conditions; wherein, (a) is the pure water evaporation mass of the sample under 0.5 sunlight; (b) is the evaporation rate and efficiency of the sample under 0.5 sunlight; (c) is an optical photograph of CFrGO / 2.5 before and after oven drying at 60°C; (d) is the temperature-time curve of dried CFrGO / 2.5 under 0.5 and 1 sunlight; (e) to (i) are temperature-time curves and thermal imaging photographs of sample evaporation experiments under 0.5 sunlight, wherein, (e) represents CFrGO / 1, (f) represents CFrGO / 2, (g) represents CFrGO / 2.5, (h) represents CFrGO / 3.3, and (i) represents CFrGO / 5.

[0042] Figure 8The figures are test results of the salt resistance and desalination performance of the CFrGO aerogel provided by the present invention; wherein, (a) to (d) are respectively the evaporation rates of CFrGO / 2.5 in 3.5wt%, 10wt%, 20wt% and 23wt% simulated seawater under one sunlight; (e) is the evaporation rate of CFrGO / 2.5 in actual Bohai Sea water; (f) is the concentration of common major cations in the original Bohai Sea water and the collected purified water; (g) is an optical photograph of the evaporation of CFrGO / 2.5 in simulated seawater of different concentrations and Bohai Sea water; (h) and (i) are respectively the structural schematic diagram and optical photograph of the homemade seawater desalination device.

[0043] Fig. 9 This is a simulation schematic diagram of the interface evaporation system experimental device provided by the present invention.

[0044] Fig.10 This is a graph showing the IW ratio of the CFrGO aerogel provided by the present invention and in pure water; wherein, (a) represents pure water, (b) represents CFrGO / 1, (c) represents CFrGO / 2, (d) represents CFrGO / 2.5, (e) represents CFrGO / 3.3, and (f) represents CFrGO / 5.

[0045] Fig.11 This is a graph showing the water evaporation rate and efficiency results of 12 cycle evaporation tests on the CFrGO / 2.5 aerogel provided by the present invention.

[0046] Fig.12 This is a graph showing the evaporation rate results of the repeated cycle test of the CFrGO / 2.5 aerogel in 20wt% concentration brine provided by the present invention. DETAILED DESCRIPTION

[0047] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0048] It should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprising", "including", "having", "containing" are used in this specification, it is indicated that there are features, steps, operations, devices, components and / or combinations thereof, which are all open terms, that is, it means including but not limited to. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the range.

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example

[0051] like Figure 1 As shown, this embodiment provides a method for preparing a hierarchical porous Janus structure carbon-graphene aerogel (CFrGO), using the following raw materials:

[0052] Chitosan ((C6H 10 NO4) n , analytically pure AR, viscosity 50-800, Sinopharm Chemical Reagent Co., Ltd.), furfural (C5H4O2, analytically pure AR (99%), Shanghai McLean Biochemical Technology Co., Ltd.), acetic acid (C2H4O2 analytically pure AR, Sinopharm Chemical Reagent Co., Ltd.), graphene oxide dispersion (1-6 layers, 10 mg / ml, water solvent, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.), nitrogen (99.99 vol%, Wuhan Shuxing Oxygen Co., Ltd.), deionized water homemade. 10 mg / mL graphene oxide dispersion was diluted with deionized water to 1, 2, 2.5, 3.3, 5 mg / ml for use, and glacial acetic acid was diluted in deionized water to a 2 wt% solution for use as a solvent. Other chemicals were used as is without further purification.

[0053] The specific preparation steps are as follows:

[0054] (1) Construction and regulation of Janus structure

[0055] Chitosan powder was dissolved and dispersed in 100ml of 2wt% glacial acetic acid aqueous solution at a mass ratio of 2:100, and stirred at room temperature 24°C until the powder was completely dissolved to form a light yellow sol. Take 100ml of diluted graphene oxide GO dispersion and add it dropwise to the above-obtained sol solution with a pipette while stirring. Continue stirring for 20min until a suspension of rGO sheets is formed, and then add furfural at a mass ratio of 1:4 dropwise. Continue stirring until completely mixed, and then pour the mold after obtaining a viscous sol. The mold uses a homemade square mold with a diameter of 14cm, a height of 2cm, and a copper block at the bottom. After pouring the mold, let it stand in an open state for 12h, waiting for the rGO sheets to slowly deposit to the bottom of the mold to form a layer. At the same time, volatilize the excess acetic acid. At this time, the sample forms a double-layer structure. The upper layer is a light yellow chitosan-furfural sol, and the lower layer is a layer formed by random stacking of brown-black rGO sheets. By changing the content of graphene oxide dispersion, the width of the rGO layer is changed, and then the thickness of the hydrophobic layer and the photothermal conversion layer in CFrGO is regulated to study its effect on the evaporation performance of CFrGO. The samples with GO dispersion concentrations of 1, 2, 2.5, 3.3, and 5 mg / ml were named CFrGO / 1, CFrGO / 2, CFrGO / 2.5, CF / rGO3.3, and CFrGO / 5, respectively. At the same time, a sample without adding GO dispersion was set as a control, named CF, and a sample without adding furfural was named CrGO. The upper chitosan-furfural sol layer subsequently becomes the hydrophilic layer of the Janus structure.

[0056] (2) Ice crystal template method freeze casting honeycomb directional pore structure hydrophilic layer

[0057] A copper block was placed in a -86℃ refrigerator to cool down, and the stratified sample was placed on the copper block. The copper block at the bottom of the mold fits tightly with the low-temperature copper block placed in the refrigerator, and the copper block is used to achieve rapid cooling. A homemade insulation cotton cover was placed on the sample to ensure that the bottom of the sol is quickly cooled by the cold source, while reducing the cooling rate around the sample, which is conducive to the vertical growth of the ice crystal template along the direction perpendicular to the cold source. Directed freezing casting of directional pore structure by ice crystal template. After freezing to form gel, the sample was placed in a freeze dryer (LQJ-20FQ, Beijing Yaxing Instrument Company) and freeze-dried from -45℃ to 30℃ with a gradient of 5℃. Each temperature gradient was maintained for 300min, and chitosan-furfural-graphene hybrid organic aerogel was prepared. At the same time, a sample randomly frozen and prepared by a mold without a copper block was set up and named CFrGO / 2.5R. CFrGO / 2.5R and CFrGO / 2.5 use the same sample formula.

[0058] (3) Carbonization

[0059] The obtained organic aerogel was placed in a high-temperature pyrolysis furnace (VBF-1200X, Hefei Kejing Material Technology Co., Ltd.), filled with N2 inert protective gas, and heated from room temperature to 300°C at a rate of 2°C / min, and then heated to 800°C at a rate of 4°C / min and maintained for 120min. After carbonization, it was annealed to 500°C at a rate of 2°C / min, and then naturally cooled to room temperature to form Janus structure CFrGO aerogel.

[0060] The stacked rGO sheet structure layer deposited in the mold is used as the light-to-heat conversion layer whose upper part contacts the light during the solar interface evaporation process.

[0061] Test Example 1

[0062] This test example characterizes the sample of the hierarchical porous Janus structure carbon-graphene aerogel prepared in the example, and the specific method is as follows:

[0063] Raman spectrometer (Horiba LabRAM HR Evolution, Japan) and X-ray diffractometer (BrukerD8 Advance, Germany) were used to characterize the internal crystal morphology of CFrGO. Surface area and pore size analyzer (JW-BK200, China, BET) were used to characterize the specific surface area and pore size distribution. UV-visible near-infrared spectrophotometer (PE lambda 75, USA) was used to measure the light absorption of the photothermal conversion layer of CFrGO samples in the wavelength range of 200-2500nm. After gold spraying treatment, the microstructure of CFrGO samples was observed using a Zeiss Sigma 300 (Germany) scanning electron microscope (SEM). Infrared spectrometer (Thermo Scientific Nicolet 6700, USA) was used to characterize the chemical composition of the samples. A synchronous thermal analyzer (STA2500, Germany) was used to analyze the thermal stability of CFrGO and determine the volatilization temperature range of adsorbed water in wet CFrGO. The anisotropic thermal conductivity of the hydrophilic layer of the directional pore structure was measured by the transient plane heat source method at room temperature (24°C) using a thermal conductivity tester (Hot Disk 2500S, Sweden), and the thermal conductivity of the rGO layer of the sample was measured by the transient hot wire method. The contact angles of the hydrophilic and hydrophobic layers of CFrGO were measured by a contact angle analyzer (SDC-3540H, China) to characterize its hydrophilicity and hydrophobicity. The interfacial evaporation rate of the sample was tested by simulating sunlight using a xenon light source (CEL-S500 / 350, China). The temperature of the entire evaporation process, including the highest and average temperatures of the region, was recorded in real time using an infrared imager (Fluke RSE60H, USA). The mass of the material and the amount of water mass reduction during the evaporation experiment were measured using a precision electronic balance (JDJS-A5+M, China). The ion composition of the pure water collected by evaporation was analyzed using an ICP analyzer (Agilent 7800(MS), USA). The drying and carbonization shrinkage were calculated by measuring the diameter of each sample before and after drying and carbonization. The bulk density was determined by dividing the weight by the volume. The linear shrinkage of atmospheric pressure drying and carbonization was calculated according to equations (1) and (2).

[0064]

[0065]

[0066] Where L 01 , L a1 is the diameter of carbon aerogel before and after atmospheric pressure drying test (mm), L 02 , L a1 is the diameter of carbon aerogel before and after carbonization test (mm).

[0067] The carbonization mass reduction rate of carbon aerogel is calculated by formula (3).

[0068]

[0069] Where M0 and Ma are the masses of carbon aerogel before and after carbonization, respectively.

[0070] Test Example 2

[0071] This test example conducts a sample evaporation experiment on the layered porous Janus structure carbon-graphene aerogel prepared in the embodiment. The specific method is as follows: a xenon light source with a diameter of 5 cm is used to irradiate the CFrGO aerogel sample floating on the liquid surface. The experiments were conducted in the laboratory at the laboratory ambient temperature (24±3°C) and relative humidity (43%±5%). In the pure water evaporation test, simulated sunlight is directly irradiated on the liquid surface. In the interface evaporation test, the surface diameter of the sample can completely cover the simulated light spot to avoid direct irradiation of the liquid surface. The simulation schematic diagram of the interface evaporation system experimental device is shown in the figure. Fig. 9 As shown. The temperature and water mass changes of the sample were monitored in real time by an infrared thermal imager and a precision electronic balance connected to a computer. When the surface temperature of the sample reached equilibrium, the mass of the remaining water during the evaporation process was recorded every 15 seconds using an electronic balance. The curve of the evaporation mass of water over time was obtained. The evaporation rate of the sample was calculated by formula (4), where m is the water evaporation rate of CFrGO (kg m -2 h -1 ), M is the water evaporation mass (kg), S is the photothermal conversion area (m 2 ), t is the light absorption time (h).

[0072]

[0073] In order to test the evaporation enthalpy and evaporation efficiency of the sample, the evaporation rate (m waterdark ) and the evaporation rate of CFrGO in the dark state (m CFrGOdark ), and the equivalent evaporation enthalpy of water in the sample is calculated by equation (5).

[0074] U in =ΔH water ×m waterdark =ΔH CFrGO ×m CFrGOdark (5)

[0075] Among them U in Represents the energy power input from the environment. In the dark state, the energy input from the outside to the material is consistent. The initial water temperature is controlled at 24°C, ΔH water The evaporation enthalpy of pure water is 2450 J / g, ΔH CFrGO is the equivalent evaporation enthalpy of water in the CFrGO sample, mCFrGOdark To obtain the equilibrium evaporation rate of water in the CFrGO sample in the dark state, the evaporation rate of water in the dark state needs to be subtracted.

[0076] The ΔH obtained above CFrGO The solar steam conversion efficiency (η) of CFrGO was further calculated and defined as Equation (6).

[0077]

[0078] Where ΔH vap (kJ kg -1 ) is the total liquid-vapor phase change enthalpy, which is calculated as formula (7). e To obtain the equilibrium water evaporation rate in the sample under illumination, it is necessary to subtract the evaporation rate of pure water without evaporating material under the same optical density conditions. The calculation formula is formula (8).

[0079] ΔH vap =ΔH CFGO +CΔT (7)

[0080] m e =mm water (8)

[0081] where q i is the incident light source density (W / m 2 ), where C(4.2kJ K -1 kg -1 ) is the specific heat capacity of water, ΔT (K) is the temperature rise of water during evaporation, and the solar steam conversion efficiency of different CFrGO samples is calculated respectively.

[0082] Analysis of test results

[0083] (1) Sample characterization results

[0084] The construction of Janus double-layer structure CFrGO carbon aerogel is inspired by the bionic inspiration of the biological "Victoria Victoria" in nature, which is hydrophobic on one side and hydrophilic on the other side, and the design characteristics of the interface evaporation material. The present invention uses chitosan, the second largest natural biomass in nature, as the matrix raw material, furfural as the cross-linking agent, and GO dispersion as the raw material for the photothermal conversion layer. Based on the precipitation process and ice crystal template freeze casting method, a three-dimensional Janus structure chitosan (chitosan)-furfural (furfural)-graphene (GO) hybrid aerogel-derived carbon-graphene composite aerogel (CFrGO) is designed and prepared for solar interface steam generation. The characteristic of chitosan is that it contains a large number of amino groups and hydroxyl groups on the carbon skeleton, and it is a natural, excellent, low-cost nitrogen-containing carbon source. In an acidic aqueous solution, the glycosidic bonds in the form of hemiacetal in chitosan will be hydrolyzed and the amino groups will be protonated and dissolved, which provides the prerequisite for chitosan to participate in the cross-linking reaction. Using 2wt% chitosan sol as the precursor solution for the reaction can reduce the density of the sample, which is of great significance for reducing the thermal conductivity of CFrGO and producing self-floating on the water surface.

[0085] Schematic diagram of Janus structure simulation of CFrGO Figure 2 As shown in (a), one side is an irregular hydrophobic layer formed by random stacking of flake graphene, and has high light absorption capacity, and the other side is a hydrophilic layer with a directional pore structure formed by cross-linking chitosan and furfural. During the sol preparation process, a large number of free amino groups in the chitosan precursor solution have strong reducing properties, and the reduction of graphene oxide (GO) is first achieved. The process of GO reduction reaction can be considered as a cross-linking reaction between the amino groups on the chitosan molecules and the large number of oxygen-containing groups on GO. The subsequent addition of furfural reacts with the remaining chitosan to form a carbonyl-amine reaction (also known as the Meilland reaction), and the more active aldehyde groups also completely reduce the residual GO at the same time. The reduced graphene oxide (rGO) is cross-linked to form a flake structure. After standing, it is deposited to the bottom under the action of gravity to form a sedimentary layer randomly stacked by rGO sheets. This process is carried out before the freeze casting process. During the freeze casting process, since the sol is placed in the mold of the bottom copper block, the temperature of the rGO deposit layer in contact with the bottom cold source drops rapidly and instantly, below the critical temperature, causing the water solvent between the rGO sheets to freeze rapidly. Therefore, the bottom rGO sheet deposit layer basically maintains the original stacking morphology after freezing. The rGO sheet layer finally has better hydrophobicity after removing the oxygen-containing groups during carbonization, becoming the photothermal conversion layer of CFrGO. Figure 2 (b) is an optical photograph of the surface and bottom of Victoria amazonica. Figure 2(c) is a top-down SEM image of the rGO layer in CFrGO. This structure simulates the microstructure formed by many tiny protrusions and depressions in the hydrophobic surface of the photosynthetic organism "Victoria Victoria" in nature. As the distance from the cold source increases, the temperature of the entire sol gradually decreases from bottom to top. At this time, the temperature is higher than the critical temperature, and the water in the sol gradually cools down and grows to form ice crystals. The ice crystals act as a template to gradually grow from bottom to top and then cast to form micron-sized directional pores. The generated ice crystals precipitate the solute in the upper layer and squeeze it to form pore walls. Figure 2 (d) and (e) are the cross-sectional top view SEM and side view SEM images of the directional pore layer of CFrGO, respectively, which simulates the structure of the hydrophilic bottom of Victoria amazonica. The directional pore layer is mainly composed of chitosan-furfural aerogel structure. Figure 2 From the top view of the directional hole in (d), it can be clearly observed that the directional hole is in the shape of a long strip, with a short side size of about 30-80 microns and a long side size of about 100-200 microns. Figure 2 In (e), the side wall of the directional hole forms a mesh-like pit structure formed by cross-linking chitosan-furfural (such as Figure 2 In (f)), the porous sidewall surface is more likely to absorb water. The micron-sized directional pore structure and the mesh pit pore structure on the sidewall surface together form a good water transmission channel due to the surface tension, providing a continuous water source for the photothermal conversion layer. Therefore, this layer structure is the hydrophilic water supply layer of CFrGO aerogel. The special hierarchical porous structure in CFrGO can significantly reduce the evaporation enthalpy, change the evaporation form of water molecules, and achieve a breakthrough of 1.47kg·m -2 ·h -1 The "theoretical evaporation limit".

[0086] In solar interfacial evaporation applications, the hydrophobic rGO photothermal conversion layer is in direct contact with sunlight. It is well known that ultra-black rGO sheets have extremely high photothermal conversion efficiency and high light absorption over a wide wavelength range. This is because rGO contains a large number of conjugated double bond structures, which can excite electrons at almost every wavelength in the solar spectrum, thereby producing various π-π* transitions. When the input light energy matches the electronic transition energy in the molecule, the electrons absorb light and transition from HOMO to LUMO. When the excited electrons are relaxed by the electron-phonon coupling, the energy is transferred from the excited electrons to the vibration mode of the entire atomic lattice, resulting in an increase in the macroscopic temperature of the material, thereby achieving a photothermal conversion effect. Moreover, the surface roughness formed by the random stacking of rGO sheets can be used to increase the light propagation path on the surface and inside of the material to form an optical microcavity, thereby increasing the light absorption area and improving the light absorption capacity. Such as Figure 2In (g), the light absorption rate in the wavelength range of 200-2500nm was measured by UV / visible / infrared spectrophotometer. In the visible light wavelength range (390nm-780nm), its absorption rate can reach more than 94%, and in the full wavelength range, the light absorption rate of CFGO can reach more than 90%, proving that its photothermal conversion interface (hydrophobic layer) has good light absorption.

[0087] The hydrophobic photothermal conversion layer in CFrGO can not only achieve efficient photothermal conversion, but also the hydrophobic interface can prevent the entry of seawater and achieve good anti-salt clogging effect. At the same time, the gaps between rGO sheets provide a good channel for steam dissipation. CFrGO as a whole can not only achieve the excellent thermal insulation effect of the aerogel structure, reduce heat loss, and improve energy utilization, but also has the good light absorption ability, photothermal conversion ability and stability of carbon materials in a wide band.

[0088] (2) Effect of GO addition on CFrGO aerogel structure

[0089] The amount of GO added is the key factor affecting the density and structure of CFrGO aerogel. Low density is of great significance for the ability of CFrGO aerogel to float on the liquid surface. In order to obtain CFrGO aerogel with low density and excellent evaporation performance, the present invention prepared and compared samples with different GO addition amounts to study their effects on the physical properties and structure of CFrGO aerogel. The results are shown in Table 1. Figure 3 . Figure 3 (a) in the figure shows the drying shrinkage, carbonization shrinkage curve and carbonization mass reduction rate curve of the CFrGO sample. It can be found that the radial shrinkage of the sample with GO added is significantly reduced compared with that of CF drying. This is attributed to the fact that the addition of rGO enhances the overall strength of the CFrGO aerogel and can better resist the surface tension generated during drying. The freeze-drying radial shrinkage of the CFrGO / 1~CFrGO / 5 samples is basically maintained at a low level below 5%. This is because during the freeze-drying process, the ice crystals between the pores of the CFrGO aerogel sublimate directly from the solid state under a high vacuum state. Compared with other drying methods such as atmospheric pressure drying and supercritical drying, freeze-drying does not exist in a liquid state, which can greatly reduce the surface tension between the pores of the CFrGO aerogel. As the amount of GO added increases, the carbonization shrinkage rate and carbonization mass reduction rate of the sample show a downward trend, proving that the addition of GO with a higher carbon content can significantly increase the residual carbon rate of the CFrGO aerogel skeleton. The increase in the amount of residual carbon can enable the carbon aerogel to maintain a higher strength carbon skeleton. Moreover, the higher skeleton strength can resist the surface tension of the tar generated during the carbonization process and reduce the shrinkage during the carbonization process. Figure 3(b) is the density statistics of the whole CFrGO aerogel sample. It can be seen that with the increase of GO addition, the sample density shows a trend of first decreasing and then increasing. The decrease in density of the early samples (CFrGO / 1~CFrGO / 2.5) is due to the decrease in shrinkage. This shrinkage includes that generated during drying and carbonization. The increase in density of the later samples is attributed to the increase in mass of the samples with higher GO addition (CFrGO / 3.3 and CFrGO / 5), which is now more dominant than the volume. CFrGO / 2.5 has the lowest density, reaching 0.0157g / cm 3 The density of all samples is about 0.0157~0.0211g / cm 3 , is generally at a lower level, so it can float freely on the liquid surface. Figure 3 (c) is an optical photograph of the CFrGO / 2.5 sample placed on a leaf. It can be seen that the low-density CFrGO / 2.5 can be easily supported by the leaf.

[0090] Figure 3 (d) to (m) show the microstructure SEM images of the rGO layer and the sidewall of the oriented pore layer of CFrGO / 1 to CFrGO / 5 samples. Figure 3 In (d) to (h), as the amount of GO added increases, the morphology of the rGO layer changes from a fluffy three-dimensional structure (CFrGO / 1) to a surface-dense compressed structure (CFrGO / 5). The stacking degree of rGO sheets becomes more and more dense, which is caused by the increase in the amount of GO added. When the amount of GO added is low, the pores between the rGO sheets are larger, and the area of ​​the rGO sheets is relatively large. Analysis of the reasons shows that this is because when GO is less, the content ratio between chitosan and GO is large. When GO contacts the chitosan sol with strong reducing properties, a rapid and violent reaction occurs, forming a larger rGO sheet structure. At the same time, the rGO sheets with less content can still maintain a large gap after being deposited to the bottom. However, with the increase in the amount of GO added, the content ratio of this reactant gradually decreases, the reaction rate slows down, and a smaller rGO sheet is formed. However, the densely stacked structure formed after the deposition of a large number of rGO sheets may cause the vapor dissipation channel of CFrGO aerogel to be blocked by rGO sheets. Therefore, it has an adverse effect on the interfacial evaporation application of CFrGO aerogel. In contrast, the stacking state and gap degree of the CFrGO / 2.5 sample are just in a relatively balanced position. This irregular sheet stacking state is believed to be conducive to the absorption of light through multiple scattering and reflection.

[0091] contrast Figure 3In (i) to (m), the pore depth of the mesh pit structure on the side wall of the directional pore layer of the CFrGO aerogel shows a downward trend. The side wall of the directional pore tends to be smooth. Moreover, the mesh gradually becomes wider. This is because this special cross-linked pore structure is obtained by the cross-linking reaction of chitosan and furfural. As the amount of GO added increases, the remaining chitosan content participating in the reaction decreases, resulting in the weakening of the cross-linked structure. Since the lower layer is a hydrophilic water supply layer, the reduction of the side wall pore structure weakens the surface tension of water, which has a certain negative effect on the transmission of water. In summary, CFrGO / 2.5 has low density and excellent structure.

[0092] (3) Composition analysis of CFrGO aerogel

[0093] In order to analyze the composition of CFrGO aerogel, the present invention further characterized the sample, and the results are shown in Figure 4 . Figure 4 (a) is the Raman spectrum of CFrGO. It can be seen that the Raman spectrum of the CFrGO aerogel as a whole is at 1350 cm -1 and 1600cm -1 There are two obvious peaks near the surface, corresponding to the D band and G band of the C element, respectively. The intensity ratio of ID / IG is highly correlated with the average size of the sp2 domain and the degree of carbon disorder. The ID / IG ratio of the CFrGO sample is about 1.2, indicating that the CFrGO aerogel is completely carbonized and has amorphous characteristics. Unless otherwise stated, the characterization uses the CFrGO / 2.5 aerogel sample as a representative. XRD was further used to analyze the crystalline structure of the rGO photothermal conversion layer and the directional pore structure hydrophilic layer of the CFrGO aerogel, as shown in Figure 2. Figure 4 As shown in (b), it can be seen that the double-layer structure of CFrGO aerogel has a broadened peak band representing graphite carbon near 2θ=22°, indicating the amorphous characteristic mode in CFrGO aerogel. The main component of CFrGO aerogel is amorphous carbon, which corresponds exactly to the result of Raman spectroscopy. In addition, energy dispersive spectroscopy (EDS) describes Figure 4 The presence of C, O, N and Au in (c). The Au element is caused by gold spraying in SEM testing. CFrGO is a carbon aerogel, and its skeleton is mainly composed of C elements. Compared with other materials, CFrGO aerogel does not contain other heavy metals or other toxic elements (such as Ti, Ni, Ag, Pt, Cu, Se, Sn, S, etc.).

[0094] In order to prove that CFrGO aerogel is a structure formed by the reaction of chitosan with furfural and GO, characterizing the changes of its chemical groups and monitoring the newly generated chemical groups is an effective means. Figure 4The curves a to f in (d) show the characteristic FTIR spectra of chitosan, uncarbonized CF, uncarbonized CrGO, uncarbonized CrGO / 2.5, CrGO and CrGO / 2.5, respectively. Chitosan has a peak at 1653 cm -1 and 1598cm -1 The characteristic absorption peaks correspond to the stretching vibration absorption peak of the primary amine (CN) and the shear vibration absorption peak of the amine group (C-NH2), at 2918 cm -1 and 3479cm -1 The characteristic absorption peaks at belong to the stretching vibration absorption peaks of the NH bond in the amine group and the stretching vibration absorption peaks of the OH bond in the hydroxyl group, which are the original characteristic chemical group FTIR spectrum data of chitosan before chemical cross-linking reaction. Comparing the four curves a, b, c, and d, it is obvious that the peak intensity of the absorption peaks of the primary amine group (CN) and the amine group (C-NH2) is significantly weakened. It proves that the amine group can undergo reduction reaction and cross-linking reaction with GO and furfural, respectively. The FTIR spectra of curves b to d show that at 1541~1543cm -1 and 1405cm -1 New characteristic absorption peaks appeared near the stretching vibration absorption peaks of C=N bond and tertiary amine (CN), which largely indicated that the cross-linked network structure in CF origin, CrGO organic and CrGO / 2.5organic has been formed. And the absorption peak intensity of C=N and CN in curves b to d showed an increasing trend, proving that with the addition of GO and furfural, the cross-linking degree of chitosan deepened successively. Compared with curves ad at 1000-1300cm -1 The stretching vibration of the CO bond at 1750 cm-1 is getting stronger and stronger, proving that the content of CO bonds is getting higher and higher. Comparing the two carbon FTIR spectrum curves e and f, most of the organic groups are removed during the carbonization process, proving that they are completely carbonized at 800°C. On the other hand, considering the safety issues of future applications of CFrGO aerogels, the present invention conducted an experimental test on whether there are any furfural crosslinking agents remaining in the CFrGO aerogels. Comparing curves d and f, no aldehyde group (HC=O) was found at 1750 cm-1. -1 The characteristic absorption peak of chitosan was shown in Figure 2. This proves that chitosan reacted fully with furfural and GO, so there was no furfural and aldehyde residue in the final CFrGO aerogel sample.

[0095] (4) Characterization of physical properties of CFrGO aerogels

[0096] CFrGO aerogel has a double-layer pore structure. At 77K, the SSA and pore size distribution of the rGO photothermal conversion layer and the hydrophilic oriented pore layer in the CFrGO aerogel were determined by static static volumetric method. The nitrogen adsorption isotherm and pore size distribution curve are shown in Figure 2. Figure 4 As shown in (e) and (f) in the figure. The adsorption amount of the rGO layer sample is relatively high during the initial adsorption (P / P0<0.1), which indicates the presence of a large number of micropores. In the later stage, the adsorption isotherm rises slowly, there is an inconspicuous hysteresis loop and no saturated adsorption platform. According to the classification of adsorption-desorption isotherms by the International Union of Pure and Applied Chemistry, the isotherm of the rGO layer belongs to the typical type I in the IUPAC classification. Figure 4 As shown in (f), the pore size distribution curve clearly shows that the pore size of the rGO layer sample is concentrated in the range of less than 10nm, proving that the rGO sheets in the CFrGO aerogel are micro- and mesoporous materials. Combined with the SEM image ( Figure 2 In (c), the rGO sheets are stacked to form macroporous gaps. This multi-level pore structure has a positive effect on enhancing the light absorption capacity and thermal insulation effect of CFrGO aerogel. The adsorption amount of the oriented pore layer sample is low during the initial adsorption, there is no hysteresis loop and no saturated adsorption platform, which is a typical type III curve. Therefore, the oriented pore layer is a macroporous structure. According to the pore size distribution curve, the oriented pore layer still has a certain micro-mesoporous structure. Combined with Figure 2 As shown in (d) to (f) in the figure, there are a large number of micron-sized pores in the oriented pore layer formed by ice crystal template casting, and there is a network of pit pore structures on the oriented pore walls. This result corresponds exactly to the BET result.

[0097] One of the design principles of interfacial evaporation materials is to have an excellent thermal insulation structure to reduce heat loss and improve energy utilization. CFrGO has an aerogel structure. After photothermal conversion occurs, its thermal insulation structure can concentrate heat. Therefore, the thermal conductivity of CFrGO / 2.5 aerogel was tested to characterize its thermal insulation performance. The hydrophobic layer of the Janus double-layer structure CFrGO aerogel is the surface layer formed by stacking rGO sheets, which can be considered to be isotropic. Figure 4 As shown in (g), the thermal conductivity of the rGO layer is 0.036W / (m·K). The hydrophilic layer of CFrGO aerogel has anisotropic characteristics as a directional pore structure, with an axial thermal conductivity of 0.081W / (m·K) and a radial thermal conductivity of 0.014W / (m·K). In general, the thermal conductivity of CFrGO aerogel is at a relatively low level. Therefore, CFrGO aerogel can show a good local heat accumulation effect after absorbing sunlight and converting light into heat.

[0098] In order to prove that CFrGO aerogel has a Janus double-layer hydrophilic-hydrophobic structure, the contact angle between the water droplet and the aerogel was obtained using a contact angle analyzer. Figure 4 (h) is a contact angle test diagram of the hydrophobic layer formed by stacking rGO sheets. The contact angle of the hydrophobic layer reaches 136.3°, showing hydrophobic properties. Therefore, the hydrophobic layer can effectively prevent seawater from entering, prevent the pores from being blocked due to the residual salt after the evaporation of seawater, and provide a smooth channel for steam to escape. Figure 4 (i) in the figure is the contact angle data diagram of the hydrophilic surface, with the horizontal axis being the frame rate and the vertical axis being the contact angle. The contact angle analyzer is set to shoot at a rate of 200 frames per second. It can be seen that when the droplet contacts the hydrophilic surface, the contact angle is about 60.5°, and the contact angle quickly changes to 0° within 6 frames (6 / 200 seconds). The sample exhibits extremely fast water absorption ability, proving the super-hydrophilicity of the hydrophilic layer. Therefore, the hydrophilic layer can quickly and continuously supply water to the upper layer. At the same time, due to its super-hydrophilicity, the residual salt after the evaporation of seawater can be quickly dissolved back into the larger water body.

[0099] The thermal stability of CFrGO was analyzed using a synchronous thermal analyzer in air atmosphere. Figure 4 (j) in the figure shows the TG and DTG curves of CFrGO aerogel in the range of 0 to 1000°C. CFrGO aerogel has a slight mass decrease process and a small endothermic peak in the range of 0 to 79.9°C. This is caused by the volatilization of water during the heating process. The hydrophilic layer of CFrGO aerogel is very easy to adsorb water vapor in the air. CFrGO aerogel began to show a significant mass decrease and endothermic peak around 345.5°C, indicating that the carbon skeleton began to thermally decompose at this time. It can be seen that CFrGO aerogel can withstand high temperatures of at least 300°C. The thermal stability of CFrGO aerogel is sufficient to ensure its application in the interfacial evaporation process. Therefore, CFrGO aerogel will not suffer thermal damage during the evaporation process. In order to prove that CFrGO aerogel can effectively promote the evaporation of water, the present invention measured the TG and DTG curves of wet CFrGO aerogel and pure water. Figure 4 In (k) and (l), it can be clearly observed that the adsorbed water in the wet CFrGO aerogel has completely evaporated at around 97.2°C. However, pure water needs to evaporate completely at around 132.5°C. This is due to the local thermal accumulation effect of CFrGO aerogel and the reduction of water evaporation enthalpy promoted by CFrGO aerogel.

[0100] (5) Equivalent evaporation enthalpy and evaporation performance test of CFrGO aerogel

[0101] In addition to its good thermal insulation effect, CFrGO aerogel can significantly improve the evaporation efficiency by promoting the reduction of water evaporation enthalpy. According to the calculation formula (6) of solar steam conversion efficiency, in one sunlight (100mW / cm 2 ) When the incident light source density is 1.47 kg·m-2 ·h -1 The reduction of evaporation enthalpy can achieve a higher evaporation rate. Therefore, the present invention adjusts the structure of CFrGO aerogel by changing the amount of GO added to adjust the evaporation state of water. The results are as follows Figure 5 As shown. Figure 5 As shown in (a), the present invention measured the evaporation rates of five samples CFrGO / 1 to CFrGO / 5 in the dark state, and then calculated the equivalent evaporation enthalpy of the samples respectively by formula (5). As the amount of GO added increases, the evaporation rate of water in CFrGO aerogel shows an interesting phenomenon of first increasing and then decreasing. The results show that the equivalent evaporation enthalpy of CFrGO / 1 to CFrGO / 5 samples is approximately 1267, 1143, 1030, 1458, and 1730 kJ kg -1 The reason is mainly related to the unique Janus structure of CFrGO aerogel. On the one hand, a large number of nano-scale micropores and mesopores are formed in the hydrophobic layer by the rGO sheets themselves and during the lamination process. This conclusion is Figure 4 The BET test results of (e) and (f) can be obtained. These pore structures form special hydrophobic nanoconstrained water molecule channels, which promote the evaporation of water molecules in the form of clusters, thereby reducing the evaporation enthalpy of water. However, with excessive addition of GO (CFrGO / 3.3~CFrGO / 5), an overly dense surface and an overly thick hydrophobic accumulation layer are formed. Therefore, the steam dissipation channel is blocked, which has a negative impact on the evaporation morphology of water. This inference is consistent with the SEM image ( Figure 3 On the other hand, the high porosity structure and hydrophilic groups in the hydrophilic layer are actively hydrated by water molecules through electrostatic and hydrogen bonding. The water molecules next to the bound water interact with less than 4 water molecules, thus forming "weakly bonded" water (IW). IW requires much less energy to evaporate than free water (FW) due to the reduced hydrogen bond density between water molecules. Therefore, the formation of IW is conducive to the reduction of evaporation enthalpy. However, with the increase in the amount of GO added (CFrGO / 1~CFrGO / 5), the contact area between the hydrophilic layer and water decreases, thereby forming less IW. There are two main reasons for this. One is the decrease in the proportion of the hydrophilic layer, and the other is that the mesh pit pore structure on the side wall of the hydrophilic layer tends to be smooth, resulting in a decrease in the contact between the hydrophilic layer and water per unit area. This evidence can be seen from the SEM image ( Figure 3(i)~(m)) in the figure. However, it is worth noting that the reduction in contact area means that there is less water around the CFrGO aerogel, which is beneficial to confine the heat inside the CFrGO aerogel and reduce the heat loss to the larger water body. Therefore, the change in the equivalent evaporation enthalpy of CFrGO aerogel is the result of the combined effect of the above two structural factors. It can be inferred that the evaporation form of water in the CFrGO aerogel is divided into two processes. First, a large amount of active IW is produced through the hydrophilic layer, and then under the photothermal drive, it passes through the hydrophobic nano-constrained water molecule channel to form water molecule clusters and evaporate. In order to support the above hypothesis, the present invention uses the OH bond stretching vibration peak in the Raman spectrum to analyze the proportion of IW in the CFrGO aerogel as a whole and in pure water. As shown Figure 5 In (b) and (c), the main peak is obtained by Gaussian fitting curve to obtain four sub-peaks. The two peaks at the lower band represent tetrahedral hydrogen bond configuration and single donor hydrogen bond configuration water, which are mainly related to FW. The two peaks at the higher band represent single hydrogen bond configuration and non-hydrogen bond water, which are mainly related to IW. Compared with pure water (IW: FW = 0.585), the proportion of IW in CFrGO aerogel is higher than that of pure water (such as Fig.10 ), which can effectively reduce the evaporation enthalpy, and the highest CFrGO / 2.5 reaches 1.302. Under one sun (100mW / cm 2 ), the data of evaporation and illumination time within 60 minutes are as follows Figure 5 As shown in (d) in the figure. As shown in the evaporation curve, the evaporation amount of the sample increases almost linearly with the increase of illumination time, indicating that its evaporation rate is very stable. In contrast, the evaporation amount of the CFrGO aerogel sample is obviously much higher than that of pure water. Figure 5 As shown in (e) in Figure 2, the evaporation rate of CFrGO / 2.5 in pure water reaches a maximum of 3.66 kg·m -2 ·h -1 , the evaporation efficiency reaches 97%. The evaporation rate of CFrGO / 2.5 is 12.2 times that of pure water. Figure 6(a) to (f) in the figure are temperature field distribution diagrams of CFrGO / 1 to CFrGO / 5 and CFrGO / 2.5R during evaporation. Under the circular simulated sunlight spot, the central temperature of the illuminated part is higher, while the temperature of the surrounding water body has only a small change. It can be seen that CFrGO aerogel can effectively locate solar heat at the interface and minimize the heat loss of heating large water bodies. The central maximum temperature and regional average temperature of CFrGO / 1 to CFrGO / 5 samples both show an upward trend. The central maximum temperature of CFrGO / 5 reached 60.9℃. Analysis of its structure shows that the rGO layer of CFrGO / 1 to CFrGO / 5 is getting wider and wider. As the proportion of rGO layer increases, the light absorption effect and thermal insulation effect of CFrGO aerogel also increase. When the amount of GO added is small (CFrGO / 1 to CFrGO / 2.5), the evaporation rate and efficiency of CFrGO aerogel samples increase with increasing temperature, which is caused by higher energy input. However, the evaporation rates of CFrGO / 3.3 and CFrGO / 5 samples decreased. The reason is that the excessive accumulation of rGO sheets blocked the pores for vapor dissipation, greatly reducing the evaporation rate and efficiency.

[0102] In order to prove that the pore structure of the hydrophilic layer of CFrGO aerogel can achieve a good water supply effect. At the same time, the present invention compares the sample CFrGO / 2.5R prepared by random freezing. The hydrophilic layer of CFrGO / 2.5R is a random directional pore structure cast by ice crystals growing in random directions. Comparing the temperature field distribution of the two samples, the results of the maximum temperature in the center and the average temperature in the region are similar (such as Figure 6 (c) and (f) in the figure). The reason is that the rGO layer structure and content of the two samples are similar. However, the evaporation efficiency and rate of CFrGO / 2.5R are lower than those of CFrGO / 2.5. This proves that the water supply of the directional pore structure is one of the key factors for efficient evaporation. The high evaporation rate of CFrGO aerogel is due to the efficient photothermal conversion and good water supply.

[0103] In order to characterize the recyclability of CFrGO aerogel, the present invention tests the water evaporation rate and efficiency of CFrGO / 2.5 sample in 12 cycles of evaporation test (e.g. Fig.11 After each evaporation, the sample was dried in a 60°C oven. In 12 cycles, the maximum evaporation rate of CFrGO / 2.5 was 3.66 kg·m -2 ·h -1 The minimum evaporation rate is 3.43 kg·m -2 ·h -1 The CFrGO / 2.5 sample still has 3.65kg·m even after the 12th cycle. -2 ·h -1Compared with the previous statistical data, there is basically no significant change, which further confirms that CFrGO aerogel has good evaporation stability and recyclability.

[0104] (6) Low-light evaporation and photothermal response performance of CFrGO aerogel

[0105] Affected by the season or region, the ambient light intensity is usually much lower than 1 sun. Therefore, interface evaporation materials with high evaporation rates under weaker light intensity are more suitable for applications in actual natural environments. The evaporation performance test and temperature response curve of the sample under low light conditions are shown in Figure 2. Figure 7 As shown. Figure 7 As shown in (a) and (b), the CFrGO / 1 to CFrGO / 5 samples were tested under 0.5 sun conditions (50 mW / cm 2 ) evaporation amount, evaporation rate and efficiency. Under low optical density conditions, CFrGO aerogel still maintains a very stable evaporation rate. CFrGO / 2.5 shows the highest evaporation rate of 1.79 kg·m -2 ·h -1 The evaporation efficiency reached 94%. After evaporation, the sample was dried in a 60°C oven, and no deformation or cracks occurred in the sample (such as Figure 7 (c) in the figure). This proves that CFrGO aerogel has good recyclability and reusability. In addition, thanks to the high light absorption rate and fluffy and porous stacking structure of rGO, CFrGO aerogel also exhibits fast photothermal response performance. The surface temperature of CFrGO aerogel during evaporation was recorded using an infrared thermal imager. Figure 7 (d) in the figure tests the photothermal response speed of dry CFrGO aerogel under 0.5 and 1 sun. The temperature of dry CFrGO aerogel basically reaches the thermal equilibrium temperature in less than 100 seconds, and the temperature still rises slightly even after long-term irradiation. Under 0.5 sun, the temperature of dry CFrGO aerogel rises from 27°C to an equilibrium temperature of 92.5°C. Under 1 sun, dry CFrGO aerogel can even reach an equilibrium temperature of 115°C. The thermal stability of CFrGO aerogel is sufficient to withstand this temperature without being damaged. Figure 7(e) to (i) in the figure record the central maximum temperature rise curve and the regional average equilibrium temperature during the evaporation process of CFrGO / 1 to CFrGO / 5 samples under 0.5 suns. The temperature of the samples floating on the liquid surface rises rapidly at the moment of exposure to light, showing sensitive photothermal response performance. The sample can still quickly reach the equilibrium temperature in about 300 seconds. The equilibrium temperature of the CFrGO aerogel surface is 40.8 to 45.5°C (±0.5°C), which is much lower than the equilibrium temperature of dry CFrGO aerogel. It proves that this part of the heat is used to drive the evaporation of water. It further shows that the efficiency of CFrGO aerogel in converting solar energy into water vapor is very high.

[0106] (7) Salt resistance and seawater desalination performance of CFrGO aerogel

[0107] Salt scale blockage usually restricts the long-term use of evaporation materials. Thanks to the carefully designed Janus structure, CFrGO aerogel has excellent salt resistance and seawater desalination capabilities. The directional pore structure hydrophilic layer in CFrGO aerogel can continuously provide moisture to the photothermal conversion layer (hydrophobic layer), and the superhydrophilicity can enhance the salt ion exchange capacity between the pore channel and the large water body. The present invention tested the evaporation performance of CFrGO / 2.5 aerogel in simulated seawater with a salinity of 3.5wt% (the average salinity of the world's oceans). The results are as follows: Figure 8 As shown. Figure 8 As shown in (a), the evaporation rate of CFrGO aerogel is only slightly lower than that of pure water. After 6 hours of continuous evaporation test, the evaporation rate of CFrGO aerogel remains stable, and no salt scale appears on the surface (such as Figure 8 (g) in the present invention). Further, the present invention tests the evaporation data of CFrGO aerogel in brine with higher concentration, such as Figure 8(b) to (d) in the figure. The evaporation rate of CFrGO aerogel in 10% brine is almost maintained at the same level as the evaporation rate of 3.5wt% simulated seawater. The evaporation rate of CFrGO aerogel did not show a significant decrease, and no salt scale appeared on the surface. This is due to the hydrophobic layer of the Janus structure, which can well block the entry of brine, and the Marangoni effect. During the evaporation process, the hydrophilic layer of CFrGO aerogel will form a salt concentration gradient from the inside to the outside, which will accelerate the water flow inside the CFrGO aerogel, thereby increasing the diffusion rate of salt and the redissolution rate of salt. The salt ions dissolved in the saturated solution inside the CFrGO aerogel will gradually flow back to the large water body along the hydrophilic channel. At this time, the salt crystallization rate is lower than the redissolution rate, which also explains why no salt scale is produced. The salinity of the brine was further increased to test the salt tolerance limit of CFrGO aerogel. The evaporation rate of CFrGO aerogel in 20wt% brine decreased slightly and a small amount of salt scale appeared on the surface. It is worth mentioning that due to the Marangoni effect, the salt scale of CFrGO aerogel completely disappeared after standing for 12 hours. Fig.12 The evaporation rate of CFrGO aerogel in 20wt% brine was repeatedly tested and the evaporation rate remained at 2.5kg·m -2 ·h -1 It was not until the brine concentration was increased to 23wt% (close to 26.5%wt% of saturated brine) that the evaporation rate of CFrGO aerogel decreased significantly and a layer of crystallized salt appeared on the surface. At this time, the salt crystallization rate was much higher than the redissolution rate. Therefore, the decrease in evaporation rate is most likely due to the fact that salt scale blocked the water supply channel and steam dissipation channel of CFrGO aerogel. When the illumination ends and it is left to stand for a period of time, the salt scale on the surface of CFrGO aerogel can still dissolve back into the large water body. Combined with the above tests, it is shown that CFrGO aerogel can at least ensure efficient and stable evaporation applications in brine with a salt concentration of less than 20wt%.

[0108] In order to further demonstrate the application potential of CFrGO aerogel in seawater desalination and to be closer to reality, the present invention uses seawater randomly collected from the Bohai Sea for testing. The salinity of the seawater was about 2.81wt%. Figure 8 As shown in (e), CFrGO aerogel maintains stable and efficient evaporation in Bohai Sea water. In the 6-hour continuous evaporation test, the evaporation rate of CFrGO aerogel in the last hour remained at 3.01 kg·m -2 ·h -1 , and there is no salt scale (such as Figure 8(g) in the figure). Compared with simulated seawater, real seawater also contains other impurities such as silt, microorganisms, and humus. Based on the above characterization, it is proved that CFrGO aerogel has good evaporation performance and salt resistance in seawater desalination applications.

[0109] Finally, in order to test the desalination effect of CFrGO aerogel, the present invention prepared a small-scale desalination device for outdoor practical application. The structural schematic diagram and optical photos of the device are shown in Figure 2. Figure 8 As shown in (h) and (i) in the figure. Nine Fresnel lenses are assembled into the upper octagonal focusing part to achieve an all-round focusing effect, thereby increasing the light intensity on cloudy days. The internally designed evaporation disk is connected to the outside of the device through a hose, and the principle of communicating vessels is used to achieve continuous supply of seawater to the inside of the device. The CFrGO aerogel on the evaporation disk achieves efficient steam generation under light. After the water vapor contacts the inclined wall of the octagonal prism and condenses, it slides to the bottom of the evaporator by gravity to achieve the collection of pure water. The remaining brine can also be collected and discharged through the hose. The homemade seawater desalination device has the functions of self-focusing, water supply, evaporation, and collection. The present invention performs IPC analysis on the pure water collected by the device, such as Figure 8 In (f), the collected pure water is compared with the original Bohai Sea water. The four common ions (Na + , K 2 + , Ca 2+ Mg 2+ ) concentration was reduced by 3 to 4 orders of magnitude, and the ion content in the collected water was significantly lower than the maximum allowable value of the drinking water quality standards of the World Health Organization (WHO, 1‰) and the US Environmental Protection Agency (EPA, 0.5‰). 3+ , Cu 2+ ) is also far lower than the safe drinking water value specified by WHO and China's Drinking Water Hygiene Standard (GB 5749-2022). Therefore, CFrGO aerogel has excellent seawater desalination performance.

[0110] In summary, the present invention utilizes the dual chemical reaction principle of chitosan free amino groups, combines precipitation process and freeze casting method, and directly prepares a biomimetic-inspired Janus structure CFrGO aerogel through a one-pot method, effectively avoiding the complexity of multi-step preparation of Janus structure, while maintaining the excellent salt resistance and interface evaporation performance of Janus structure. Under 1 sun, CFrGO aerogel achieves 3.66 kg·m -2 ·h -1 The evaporation rate and steam generation efficiency of 97% were 1.34% and 1.22% respectively. In the salt tolerance test, the CFrGO aerogel showed a steam generation efficiency of 3.01 kg·m in Bohai seawater and 10% brine. -2 ·h -1and 3.16 kg·m -2 ·h -1 The evaporation rate is very fast and there is no salt accumulation. The good steam generation performance and salt tolerance of CFrGO aerogel are due to the following reasons:

[0111] (1) The photothermal conversion layer constructed based on rGO sheets can achieve efficient photothermal conversion, and the hydrophobic interface prevents the entry of seawater to achieve good salt resistance. At the same time, the gaps between rGO sheets provide a good channel for steam dissipation.

[0112] (2) The micrometer-sized directional pores in the hydrophilic layer and the mesh-like pit pore structure on the side wall together form a super-hydrophilic water supply channel, which promotes the rapid transmission of water. During the evaporation of brine, the hydrophilic layer will form a salt concentration gradient from the inside to the outside, which will accelerate the water flow inside the CFrGO aerogel, thereby increasing the diffusion and redissolution rate of salt.

[0113] (3) Experiments and calculations have shown that this special hierarchical porous structure in CFrGO aerogel changes the evaporation morphology of water molecules and significantly reduces the evaporation enthalpy.

[0114] (4) CFrGO aerogel has fast photothermal response performance, and its overall thermal insulation effect can achieve excellent thermal insulation effect, avoiding heat loss to large water bodies and achieving local heat accumulation.

[0115] In summary, the present invention provides an effective strategy for the development of efficient, stable and salt-tolerant SIE seawater desalination technology.

[0116] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a hierarchical porous Janus structure carbon-graphene aerogel, characterized in that: The steps include: S1. Dispersing chitosan in an acid solution and stirring until it is completely dissolved to form a sol; S2, adding the graphene oxide dispersion to the sol, stirring to form a suspension having reduced graphene oxide sheets, then adding furfural, stirring until completely mixed, and then casting a viscous sol solution; S3, after the mold is poured, the mold is left to stand in an open state, and the reduced graphene oxide sheets are deposited to the bottom of the mold to form a layer, and the sample in the mold forms a double-layer structure; wherein the upper layer is chitosan-furfural sol, and the lower layer is reduced graphene oxide sheets; S4, placing the mold on a pre-frozen copper block, and performing gradient freeze drying after the sample is frozen to form a gel, to obtain a chitosan-furfural-graphene hybrid organic aerogel; Specifically, step S4 includes: S41, pre-freezing and cooling the copper block, placing a mold on the copper block, and directional freeze-casting a directional hole structure through an ice crystal template; S42, after being frozen to form a gel, placing the sample in a freeze dryer and freeze drying it from -45°C to 30°C with a gradient of 5°C to obtain a chitosan-furfural-graphene hybrid organic aerogel; S5. Placing the organic aerogel in a high-temperature cracking furnace, filling it with inert protective gas, heating it for carbonization, annealing it after carbonization, and then naturally cooling it to room temperature to obtain a hierarchical porous Janus structure carbon-graphene aerogel.

2. The preparation method according to claim 1, characterized in that: In step S1, the acid solution is an aqueous solution of glacial acetic acid, and the mass ratio of the chitosan to the aqueous solution of glacial acetic acid is 1:(40-60).

3. The preparation method according to claim 1, characterized in that: In step S2, the concentration of the graphene oxide dispersion is 1-5 mg / ml.

4. The preparation method according to claim 1, characterized in that: Step S2 includes: S21, adding the graphene oxide dispersion liquid dropwise to the sol while stirring, and stirring until a suspension having reduced graphene oxide sheets is formed; S22, adding furfural dropwise to the suspension, stirring until completely mixed, and then casting into a mold after obtaining a viscous sol liquid.

5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of furfural to chitosan is 1:(3-6).

6. The preparation method according to claim 1, characterized in that: Step S5 includes: S51, placing the organic aerogel in a high-temperature pyrolysis furnace, filling it with inert protective gas, raising the temperature from room temperature to 300°C at a rate of 2-4°C / min, and then raising the temperature to 800-1200°C at a rate of 4-6°C / min for carbonization; S52. After the carbonization is completed, annealing is performed to 500°C at a rate of 2°C / min and naturally cooled to room temperature to obtain a hierarchical porous Janus structure carbon-graphene aerogel.

7. A hierarchical porous Janus structure carbon-graphene aerogel, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the hierarchical porous Janus structure carbon-graphene aerogel according to claim 7 in the field of seawater desalination.

Citation Information

Patent Citations

  • MXene / rGO aerogel, PDA / CS / MXene / rGO aerogel and preparation method and application thereof

    CN116351403A

  • High-salt-tolerance P (AM-DMDAAC) / graphene-based macroporous Janus aerogel as well as preparation method and application thereof

    CN117586550A